MODELING OF BUSINESS PROCESSES FOR MANAGING INTEGRATIVE DIGITAL DEVELOPMENT OF ENTERPRISES - Оlena V. Vynogradova; Svitlana V. Lehominova; Aliona Yu. Goloborodko; Tetiana I. Nosova (Academy Review)
It has been proven that the development of information and communication services enterprises is of strategic importance for the complementary growth of all sectors of the Ukrainian economy and serves as a platform for boosting and advancing proactive business segments overall. The fundamental methods for modeling business process flows using mathematical and analytical tools, specifically a system of differential equations with defined initial conditions, have been substantiated, enabling the integral assessment of enterprise business process modeling. A capsulated approach to the digitalization of business processes and a comparative analysis of a broad range of financial and economic indicators for comprehensive diagnostics of integrative enterprise development effectiveness were applied, allowing for the determination of a probable development scenario for enterprises in the future. The key flows of enterprise business processes have been identified: material, innovative- intellectual, information-marketing, and financial. The dependence of management efficiency and the achievement of positive outcomes on the synchronization of these flows has been revealed, taking into account possible temporary variations in the investment dynamics of each flow. The mathematical model for calculating profitability was tested using data from the information and communication companies PJSC «Kyivstar», PJSC «Vodafone», and LLC «Lifecell». This approach enabled the identification of the most influential streams by year and revealed patterns of leadership changes based on the impact of external environmental factors and internal organizational conditions. The dependence of achieving positive results on the configuration of financial, material, innovative and intellectual, and information and marketing flows has been identified. This analysis allowed for the proposal of management vectors for managing the integrative development of information and communication services enterprises: passive, focused, sustainable and proactive integrative development.